SHALAHUDDIN AL-’AḌLABI Analisis Metodologi Kritik Matan Hadīṡ Terhadap Riwayat Yang Bertentangan Dengan Akal, Indra dan Sejarah - Muhammad Nabat Ardli; Reza Hilmy Luayyin (Program Studi Ilmu Hadis Fakultas Ushuluddin Adab dan Dakwah IAIN Langsa, 2024)
Research on Hadīṡ cannot be separated from two main elements, called sanad and matan. Among Hadīṡ scholars, research on sanad receives more attention than matan, which prompted Salahuddin al-’Aḍlabi to write the book